Perbandingan Efisiensi Pemakaian Tower Crane dan Mobile Crane pada Gedung Bertingkat: (Studi Kasus : Proyek Rumah Susun Itera TA 2021/2022) - Fara Annisa Darma Putri; Rajiman Rajiman; Anita Lestari Condro Winarsih; Dicky Rahadianto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
A multi-storey construction project requires heavy equipment to support the process of mobilizing materials and materials. The heavy equipment that is often used as a distribution aid when carrying out building construction works are: Tower Cranes and Mobile Cranes. The ITERA RUSUN project uses a Tower Crane as a tool for lifting materials. This study aims to analyze the length of time, the cost and the difference between the time and cost required for Tower Cranes and Mobile Cranes to complete the column pouring work on the fifth floor. In this study, field observations were made with the Tower Crane, while it was used for the Mobile Crane as a comparative tool without field observations. The results of the calculation analysis revealed that the execution time of the pouring work of the fifth floor pillar using a Tower Crane was 6 hours 3 minutes 36 seconds, while the time for the Mobile Crane is 7 hours 17 minutes 24 seconds. The cost of a Tower Crane is Rp. 6,205,000.00 while the cost of a Mobile Crane is Rp. 4,677,000.00. The time difference between using Tower Cranes and Tower Cranes for the pouring work on the fifth floor column is 1 hour 13 minutes 38 seconds with a cost difference of Rp. 1,528,000.00. From the results of the calculations carried out, the use of a Mobile Crane results for casting and material lifting work in terms of costs and savings.